Δίκαιος and Cognates in Plato's Crito. - (Yossie) Liebersohn, Yosef Z. (Scripta Classica Israelica, 2023)
The term 'justice' and its cognates appear frequently enough in Plato's Crito to serve as a vehicle for all discussions of this dialogue. In this paper, I will examine the various usages of dik- in the Crito and show that, within the broad meaning of justice, each usage has a unique meaning. Only by deciphering these specific meanings can the conversation between Crito and Socrates be fully understood, and Plato's message in the Crito properly evaluated.